Silencing Srsf6 does not modulate incomplete splicing of the huntingtin gene in Huntington’s disease models - Michael A. Mason (Nature Portfolio, 2020)
Abstract We have previously shown that the incomplete splicing of exon 1 to exon 2 of the HTT gene results in the production of a small polyadenylated transcript (Httexon1) that encodes the highly pathogenic exon 1 HTT protein. There is evidence to suggest that the splicing factor SRSF6 is involved in the mechanism that underlies this aberrant splicing event. Therefore, we set out to test this hypothesis, by manipulating SRSF6 levels in Huntington’s disease models in which an expanded CAG repeat had been knocked in to the endogenous Htt gene. We began by generating mice that were knocked out for Srsf6, and demonstrated that reduction of SRSF6 to 50% of wild type levels had no effect on incomplete splicing in zQ175 knockin mice. We found that nullizygosity for Srsf6 was embryonic lethal, and therefore, to decrease SRSF6 levels further, we established mouse embryonic fibroblasts (MEFs) from wild type, zQ175, and zQ175::Srsf6 +/− mice and transfected them with an Srsf6 siRNA. The incomplete splicing of Htt was recapitulated in the MEFs and we demonstrated that ablation of SRSF6 did not modulate the levels of the Httexon1 transcript. We conclude that SRSF6 is not required for the incomplete splicing of HTT in Huntington’s disease.